The Development of Village Data and Information Management through the Innovation Diffusion - Indah Prabawati; Galih Wahyu Pradana; Muhammad Farid Ma'ruf; Badrudin Kurniawan; Deby Febriyan Eprilianto; Tolentino de Araujo Tolentino (The Journal of Society and Media, 2022)
Public services, including in villages, have begun to be directed and adjusted to the concept of data services based on information, communication, and technology (ICT). E-Monografi Desa is expected to be able to present village data profiles used to determine the characteristics of potential resources, the development of all development sectors, as well as development problems in each village and sub-district. The research was conducted in Kedung Peluk Village, Candi District, Sidoarjo Regency, using a qualitative approach. The data collection techniques used by the researcher include interviews (interviews), Focus Group Discussions (FGD), and Literature Studies. We used Rogers' Diffusion of Innovation theory to analyze the phenomena and issues discovered. Based on the results of the FGD, there are also inputs to improve the design of the E-Monografi Desa application for users.